Impact of Chemotherapy on Extracellular Vesicles: Understanding the Chemo-EVs - Ab Razak, Nur' Syahada; Ab Mutalib, Nurul Syakima; Mohtar, M. Aiman; Abu, Nadiah (Frontiers in Oncology, 2019)
Chemotherapy is the standard go-to treatment for cancer besides surgery and radiation. It has recently come to light that the interaction between chemotherapy and the immune system is important in maintaining tumor immunity as well as influencing the efficacy of the therapy. However, ample preclinical studies have shown that in addition to direct cytotoxic effects on cancer cells, a fraction of chemotherapeutic agents may promote immunogenic cell death, and alter the inflammatory milieu of the tumor microenvironment. Extracellular vesicles (EV) have been shown to interact with the tumor microenvironment by delivering alterative signals to the surrounding cells; as a result, this results in interference with each cell's capability to eradicate tumors or gives advantages to cancer cells so as to survive therapy. Chemotherapy-induced extracellular vesicles (chemo-EVs) have been theorized to be carrying different cargo loads than non-chemotherapy-induced EVs. Aside from chemoresistance, there is growing evidence to suggest that chemo-EVs could dictate tumor behavior, especially in terms of metastasis, immune response, and cancer stemness. This mini-review attempts to summarize and evaluate recent developments on the role of chemo-EVs in other aspects of tumor-related processes.